Role of gut-derived protein-bound uremic toxins in cardiorenal syndrome and potential treatment modalities - Suree Lekawanvijit (2018)
© 2015, Japanese Circulation Society. All rights reserved. Uremic toxins have been increasingly recognized as a crucial missing link in the cardiorenal syndrome. Advances in dialysis technologies have contributed to an enormous improvement in uremic toxin removal, but removal of protein-bound uremic toxins (PBUTs) by current conventional dialysis remains problematic because of their proteinbinding capacity. Most PBUTs that have been implicated in cardiorenal toxicity have been demonstrated to be derived from a colonic microbiota metabolism pathway using dietary amino acids as a substrate. Currently, indoxyl sulfate and p-cresyl sulfate are the most extensively investigated gut-derived PBUTs. Strong evidence of adverse clinical outcomes, as well as biological toxicity on the kidney and cardiovascular system attributable to these toxins, has been increasingly reported. Regarding their site of origin, the colon has become a potential target for treatment of cardiorenal syndrome induced by gut-derived PBUTs.